Demonstration of Moringa Leaf Utilization for Micronutrient Sufficiency in Stunting Prevention in Limbangan Wetan Village, Brebes Regency - Syaputra, Kurniawan Adi; Rahmanto, Dhidhin Noer Ady; Azizah, Fairuz; Pramesti, Diah; Fitriani, Fitriani; Faradita, Aulia; Ayuni, Femela Zulfa; Setyawan, Ridwan; Hasibuan, Nella Rita Suci; Ardiyanto, Ardiyanto; Tsania, Hidayatul Barika (Bangun Desa: Jurnal Pengabdian Masyarakat, 2024)
This activity was motivated by the high rate of stunting in Limbangan Wetan Village. In addition, students also provided a way to process moringa leaves using milk. Demonstration of the Utilization of Moringa Leaves as Micronutrient Adequacy in Stunting Prevention Efforts in Limbangan Wetan Village, Brebes Regency. The Moringa Milk Demonstration activity was carried out at the Limbangan Wetan Village office, Brebes District, Brebes Regency, Central Java Province. The method applied was the delivery of material and demonstration of making moringa milk delivered by students of the Nutrition and Midwifery Study Program, Alma Ata University and assisted by friends from other study programs and accompanied by a question and answer session between students and pregnant women and posyandu cadres. In this demonstration, students of Nutrition and Midwifery, Alma Ata University presented material containing: definition of stunting, differences between stunting and malnutrition, characteristics of stunting, causes of stunting, impacts of stunting, how to prevent stunting, and nutritious intake to prevent stunting. The demonstration activities yielded positive outcomes, as evidenced by the high level of enthusiasm and active participation from pregnant women in Limbangan Wetan Village. These findings suggest that community-based interventions focusing on nutrition education and stunting prevention can effectively engage target groups, highlighting the importance of continued efforts to support maternal and child health in rural areas.